El proceso de aprendizaje en el entorno natural. - Heredia Rengifo, Biviana Natali (2020)
The variations in the natural environment, can be experimented by children, as they help to the developing of the teaching learning process. Without a doubt, the contact with the nature, favors to the construction and process of internal mental schemas that in the classroom is not possible that can be built. The natural spaces, form suitable scenarios to do many activities in education, recreation and environmental sensitivity. The objective was to determine the incidence of the natural environment in the learning process of children between 4 and 5 years of the My Second Home Children's Center, in Latacunga city, Cotopaxi province, in the 2019-2020 school year. It was carried out a study with mixed approach quantitative-qualitative where it was evidenced as a result of greater significance that the continuous contact of children with nature benefit to the developing of the teaching learning process. Benefit the mental and physic children´s health getting sick less and strengthening their immune system. The contact with nature. The natural environment contributed to the concentration and attention, the autonomy develops better; the creativity, the fantasy and the reasoning. In addition, a proposal of methodological strategies was developed, as a teacher support tool to favor the contact with the nature and learning. It has been qualified to the proposal as excellent, pointing out that the scope of it can be local, because they are important strategies to the integral children´s development and offers them unique sensorial experiences with natural elements